Soleus fascicle length changes are conserved between young and old adults at their preferred walking speed - Panizzolo, F.; Green, D.; Lloyd, D.; Maiorana, Andrew; Rubenson, J. (Elsevier, 2013)
Older adults have been shown to naturally select a walking speed approximately 20% slower than younger adults. We explored the possibility that a reduction in preferred speed in older adults represents a strategy to preserve the mechanical function of the leg muscles. We examined this question in the soleus muscle in eight healthy young (25.8 ± 3.5 years) and eight healthy older adults (66.1 ± 2.3 years) who were paired so that their preferred speed differed by ~20%. Soleus muscle fascicle lengths were recorded dynamically using ultrasound, together with simultaneous measurements of soleus EMG activity and ankle joint kinematics while (a) older adults walked on a treadmill at a speed 20% above their preferred speed (speeds matched to the preferred speed of young adults), and (b) young and older adults walked at their preferred treadmill speeds. Analyses of mean muscle fascicle length changes revealed that, at matched speeds, older adults had a statistically different soleus fascicle length pattern compared to young adults, where the muscle's stretch-shorten cycle during stance was diminished. However, older adults walking at their preferred speed exhibited a more pronounced stretch-shorten cycle that was not statistically different from young adults. Conserving muscle length patterns through a reduction in speed in older adults may represent a physiologically relevant modulation of muscle function that permits greater force and power production. Our findings offer a novel mechanical explanation for the slower walking speed in older adults, whereby a reduction in speed may permit muscles to function in a mechanically similar manner to that of younger adults.